Variability in Osmotic Stress Tolerance of Starch Potato Genotypes (Solanum tuberosum L.) as Revealed by an In Vitro Screening: Role of Proline, Osmotic Adjustment and Drought Response in Pot Trials. (25th August 2016) - Bündig, C.; Vu, T. H.; Meise, P.; Seddig, S.; Schum, A.; Winkelmann, T.
Abstract: Solanum tuberosum (potato) as a drought sensitive plant is also one of the most promising plants to meet the demands for food and starch of a growing population. Distinguishing genotypes into tolerant and susceptible is therefore of utmost interest. We subjected eighteen potato genotypes and two wild species, S. tarijense and S. chacoense, to osmotic stress applied in vitro by addition of 0.2 m sorbitol to a solid medium. Here, we report that a ratio of root:shoot dry mass (DM) together with the SSI (stress susceptibility index, equivalent to drought susceptibility index by Fischer and Maurer, Aust. J. Agron. Res., 29, 1978) of shoot DM were found to be relevant parameters to characterize genotypes in vitro for their osmotic stress tolerance. Drought stress data from pot trials in a rainout shelter (2013 and 2015) correlated poorly with the data obtained in in vitro experiments. However, the most tolerant and most sensitive genotypes in vitro were also categorized to be more tolerant or sensitive than the average to drought stress in vivo . Both, under in vitro and in vivo conditions, proline displayed an increase under osmotic stress conditions in nearly all potatoes tested, but no direct correlations were found to stress tolerance. However, a genotype classified as tolerant displayed earlier proline accumulation. Proline is thought of as one factor for plants to withstand stressful conditions, but cannot be used to distinguish potato genotypes for their stress tolerance to osmotic stress in vitro . Analysis of the osmotic potential of in vitro and in vivo stressed plants displayed a general increase compared to the control.